2008
DOI: 10.1002/hup.935
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of mirtazapine and amitriptyline in alcoholic patients with co‐morbid depressive disorder: a randomized, double‐blind study

Abstract: The treatment with either mirtazapine or amitriptyline resulted with the reduction of HDRS and craving scores. The side-effect profile of mirtazapine was relatively favorable in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…The significant within-group decrease in depressive symptoms noted during the course of the current treatment trial is consistent with the within-group finding of an open label study by Yoon and colleagues (2006) conducted in South Korea and the between-group findings of a double-blind study by Altintoprak and colleagues (2008) conducted in Turkey. Both of those studies reported significant decreases in depressive symptoms in their studies of comorbid subjects involving mirtazapine.…”
Section: Discussionsupporting
confidence: 87%
“…The significant within-group decrease in depressive symptoms noted during the course of the current treatment trial is consistent with the within-group finding of an open label study by Yoon and colleagues (2006) conducted in South Korea and the between-group findings of a double-blind study by Altintoprak and colleagues (2008) conducted in Turkey. Both of those studies reported significant decreases in depressive symptoms in their studies of comorbid subjects involving mirtazapine.…”
Section: Discussionsupporting
confidence: 87%
“…We are currently using plasma levels of catecholamine metabolites to determine which antidepressant drug should be used to treat depressive patients with alcohol dependence. In a randomized double-blind study, Altintoprak et al (2008) recently found that mirtazapine is effective and well tolerated in alcoholic patients with comorbid depressive disorders. Muhonen et al (2008) reported the efficacy of memantine, a noncompetitive glutamate N-methyl-D-aspartate receptor blocker, for major depressive disorders comorbid with alcohol dependence.…”
Section: Discussionmentioning
confidence: 98%
“…High heterogeneity (Q=14.05, df=2, p<.001, I 2 =86%) persisted in the low baseline depression severity studies (n=3). Nine studies reported depression scores at multiple follow-up timepoints (Altintoprak, et al, 2008;R. A.…”
Section: Change In Depression During Treatmentmentioning
confidence: 99%
“…Follow-up completion rates in these studies ranged from 48 to 93% (median 70%). The remaining 6 studies (Altintoprak et al, 2008;Dorus et al, 1989;Janiri et al, 1996;Mason et al, 1996;Paparrigopoulos et al, 2010;Petrakis et al, 2007) were excluded from the meta-analysis because their reported outcomes were not clearly identified as relating to the intention-to-treat sample.…”
Section: Insert Table 1 About Herementioning
confidence: 99%